The age of modernism : Art in the 20th century - Joachimides, Christos M.; Rosenthal, Norman; Adams, Brooks; Fietzek, Gerti; Hughes, Henry Meyric; Bann, Stephen; Daniels, Dieter; Danto, Arthur C; Groys, Boris; Lepenies, Christos M.; Marquard, Odo; Morgan, Robert C; et al. (Ostfildern-Ruit : Gerd Hatje, 1997)
Andre, Carl ; Vacon, Francis ; Balla, Giacomo ; Balthus ; Baselitz, Georg ; Beckmann, Max ; Beuys, Joseph ; Boccioni, Umberto ; Boltanski, Christian ; Bonnard, Pierre ; Brancusi, Constantin ; Brasue, Georges ; Broodthaers, Marcel ; Burri, Alberto ; et al.
May 7 - 27 july, 1997, Martin-Gropius-Bau, Berlin
kunstcatalogus